2017
DOI: 10.1115/1.4035882
|View full text |Cite
|
Sign up to set email alerts
|

Design of Mechanisms to Draw Trigonometric Plane Curves

Abstract: This paper describes a mechanism design methodology that draws plane curves which have finite Fourier series parameterizations, known as trigonometric curves. We present three ways to use the coefficients of this parameterization to construct a mechanical system that draws the curve. One uses Scotch yoke mechanisms for each of the terms in the coordinate trigonometric functions, which are then added using a belt or cable drive. The second approach uses two-coupled serial chains obtained from the coordinate tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Our use of cubic trigonometric Bezier curves follows the formulation of Han [17], who used four control points to define a curve that has the same properties as cubic polynomial Bezier curves [18]. Therefore, in this paper, we define a system of plane curves using cubic Bezier curve segments and then use the results of Liu and McCarthy [19] to design a mechanical system that draws the curves.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Our use of cubic trigonometric Bezier curves follows the formulation of Han [17], who used four control points to define a curve that has the same properties as cubic polynomial Bezier curves [18]. Therefore, in this paper, we define a system of plane curves using cubic Bezier curve segments and then use the results of Liu and McCarthy [19] to design a mechanical system that draws the curves.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, the component functions of a degree n Bezier curve are defined by a finite Fourier series in h, which means it is a trigonometric curve [15]. Liu and McCarthy [19] showed that a trigonometric curve p(h) defined by Fourier series is given by…”
Section: Degree N Bezier Curvementioning
confidence: 99%
See 3 more Smart Citations